PREFERENSI NYAMUK (Aedes sp.) TERHADAP BERBAGAI WARNA Ovitrap SEBAGAI PENGENDALIAN POPULASI - Khansa, Anidya Annisa; Ramadhanty, Nur Alfi; Suryanda, Ade (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2021)
Backgroud: Dengue Hemorrhagic Fever (DHF) is a disease caused by Dengue virus infection and is carried or can be transmitted by mosquitoes, Aedes sp. Until now there has been no dengue virus vaccine, so efforts to eradicate dengue are still based on breaking the chain of transmission, especially human and vector components such as Mosquito Nest Eradication (PSN). Ovitrap (oviposition trap) is a tool that can be used to catch eggs and adult mosquitoes or it can also be used to detect the presence of mosquitoes. Method: This research was conducted in 2020 with a technical literature study. Result: Based on the research, it was found that the water storage container for laying eggs (Ovitrap) was the most preferred and many Aedes aegypti mosquitoes were found, namely the black ovitrap. Conclusion: There are several factors that support mosquitoes to lay eggs, one of which is the color and type of place / container. The most preferred water storage container for laying eggs (Ovitrap) and many Aedes aegypti mosquitoes is the black ovitrap. The number of eggs caught was significantly different for each ovitrap color.